Nail the Mix: Standardization in Mixing Metal Music? - Herbst, Jan-Peter; Mynett, Mark (Popular music and society, 2021)
This article explores how the proliferation of affordable digital tools and the availability of specialist knowledge have affected the mixing stage of metal music productions, asking whether a standard methodology is apparent in producers' use of templates and presets, processing of audio, and choice of tools. Analyzing fifty professional metal mixes on the platform Nail The Mix, the findings suggest that although producers follow a vaguely defined standard methodology for technical reasons, they have leeway for individuality and creativity. Producers freely give insight into their mixing approaches, which likely inspires exploration of new approaches in the metal producer community.